PERSEPSI GURU TENTANG MOODLE SERTA DAMPAK PEMBELAJARANNYA TERHADAP SISWA - Resky Indah Tantri (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2019)
This study aims to determine the teachers perception of the use of Moodle e-learning media and the impact of learning on students of State Vocational Schools in the city of Banyuwangi. The variable is the teachers perception of the use of Moodle e-learning and the impact of learning on students of State Vocational Schools in the City of Banyuwangi. This research is a qualitative research. The population used amounted to 87 teachers of State Vocational Schools in the City of Banyuwangi who used Moodle e-learning as a learning medium. Data collection in research using observation, interviews, and questionnaires. The results of the study showed that (1) individual factors led to the teacher's perception of the use of Moodle e-learning as a learning medium that was different. The concept of implementing Moodle e-learning that is used by teachers in four SMKs in the city of Banyuwangi is an asynchronous model, namely students learn independently but still communicate with the teacher; (2) the impact of learning that occurs on students according to teacher perceptions are two, namely the impact of positive learning and the impact of negative learning.